2001
DOI: 10.1161/hy1201.096573
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin AT 1 Receptor Stimulates Heat Shock Protein 27 Phosphorylation In Vitro and In Vivo

Abstract: Abstract-The angiotensin type 1 receptor (AT 1 ) exerts a variety of its signaling and cellular actions through its effects on protein phosphorylation. Phosphoproteomic analysis of angiotensin (Ang) II-stimulated aortic smooth muscle cells revealed that heat shock protein 27 (HSP27) represents a major protein phosphorylation target of the AT 1 signaling pathway. Stimulation of cells with Ang II resulted in 1.7-fold (PϽ0.05) and 5.5-fold (PϽ0.001) increases in HSP27 phosphoisoforms at pI 5.7 and pI 5.4, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…We recently reported that overexpression of Hsp27 in LNCaP cells suppressed castration-induced apoptosis and confers androgen resistance (23), whereas Hsp27 knockdown using ASO potently decreases Hsp27 levels, increases caspase-3 cleavage and apoptosis, enhances paclitaxel chemosensitivity, and delays tumor progression in vivo (22,23 . p38 kinase and Akt were reported to be the Hsp27 kinases (32,33), although protein kinase C (PKC) a and y and cyclic AMP-dependent kinase can also phosphorylate Hsp27 (43). Hsp27 becomes phosphorylated when exposed to angiotensin (43), interleukin-6 (IL-6), IL-1, heat shock and tumor necrosis factor-a (44).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that overexpression of Hsp27 in LNCaP cells suppressed castration-induced apoptosis and confers androgen resistance (23), whereas Hsp27 knockdown using ASO potently decreases Hsp27 levels, increases caspase-3 cleavage and apoptosis, enhances paclitaxel chemosensitivity, and delays tumor progression in vivo (22,23 . p38 kinase and Akt were reported to be the Hsp27 kinases (32,33), although protein kinase C (PKC) a and y and cyclic AMP-dependent kinase can also phosphorylate Hsp27 (43). Hsp27 becomes phosphorylated when exposed to angiotensin (43), interleukin-6 (IL-6), IL-1, heat shock and tumor necrosis factor-a (44).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II is shown to induce HSP27 phosphorylation through AT1-receptor activation (43). Phosphorylated HSP27 stabilizes actin filaments and plays a central role in SMC contraction.…”
Section: Biological Functions Of the Identified Proteins And Their Pomentioning
confidence: 99%
“…Angiotensin II (Ang II), the effector peptide of the rennin-angiotensin system formed as a result of sequential proteolysis of the angiotensinogen precursor, plays an important role in the development of hypertension and regulation of body fluid homeostasis. Interestingly, Ang II induces expression of Hsps in smooth muscle cell culture, aorta, and kidney (Xu et al 1995;Aizawa et al 2000;Meier et al 2001;Ishizaka et al 2002), and all suggest a protective role of Hsps against Ang II-induced end-organ injury. However, there is no direct evidence for HS treatment having an effect on Ang II-induced hypertension and inflammation.…”
Section: Introductionmentioning
confidence: 97%